2011
DOI: 10.1007/s12263-011-0257-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations between functional polymorphisms in antioxidant defense genes and urinary oxidative stress biomarkers in healthy, premenopausal women

Abstract: Functional polymorphisms in endogenous antioxidant defense genes including manganese superoxide dismutase (MnSOD), catalase (CAT), and glutathione peroxidase (GPX-1) have been linked with risk of cancer at multiple sites. Although it is presumed that these germline variants impact disease risk by altering the host's ability to detoxify mutagenic reactive oxygen species, very few studies have directly examined this hypothesis. Concentrations of 8-isoprostane F2α (8-iso-PGF2α) and 8-oxo-7,8-dihydro-2'-deoxyguano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(25 reference statements)
1
9
0
Order By: Relevance
“…The remaining 278 references could be utilized to establish the increase in 8-iso-PGF 2α levels associated with medical conditions [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83], [84], [85], [86], [87], [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102], [103], [104], [105], [106], [107], [108], [109], [110], [111], [112], [113], [114], [115], [116], [117], [118], [119], [120], [121], [122], [123], [124], [125], [126], [127], [128], [129], [130], [131], [132], [133], [134], [135], [136], [137], [138], [139], [140], [141], [142], [143], [144], [145], [146]…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 278 references could be utilized to establish the increase in 8-iso-PGF 2α levels associated with medical conditions [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83], [84], [85], [86], [87], [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102], [103], [104], [105], [106], [107], [108], [109], [110], [111], [112], [113], [114], [115], [116], [117], [118], [119], [120], [121], [122], [123], [124], [125], [126], [127], [128], [129], [130], [131], [132], [133], [134], [135], [136], [137], [138], [139], [140], [141], [142], [143], [144], [145], [146]…”
Section: Resultsmentioning
confidence: 99%
“…The number in the affected and control groups represents the number of people tested. Data for this figure was extracted from references [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83], [84], [85], [86], [87], [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102], [103], [104], [105], [106], [107], [108], [109], [110], [111], [112], [113], [114], [115], [116], [117], [118], …”
Section: Figmentioning
confidence: 99%
“…This antioxidative function of vitamin D was comparable with that of an anticancer drug, tamoxifen, and its 4‐hydroxy metabolite . Later, it was reported that the antioxidant potency of vitamin D was even more than that of Trolox (a water‐soluble analogue of vitamin E), β ‐estradiol and melatonin . These findings were further endorsed by animal studies .…”
Section: Vitamin D: Antioxidant Role In Diabetesmentioning
confidence: 99%
“…Experience and preferences of the investigators as well as the available budget and facilities are the main determinants of the methods used to evaluate OS in most cases. Components of both endogenous and exogenous antioxidant defense arms are affected by both dietary intake of essential nutrients and genetic makeup . Lack of reference interval for most, if not all, of the OS biomarkers makes the interpretation and comparison of data from different studies even harder.…”
Section: Concluding Remarks For Future Studiesmentioning
confidence: 99%